Predictors of engagement in an internet-based cognitive behavioral therapy program for veterans with chronic low back pain. Issue 6 (24th October 2020) - Solar, Chelsey; Halat, Allison M; MacLean, R Ross; Rajeevan, Haseena; Williams, David A; Krein, Sarah L; Heapy, Alicia A; Bair, Matthew J; Kerns, Robert D; Higgins, Diana M
Abstract: Internet-based interventions for chronic pain have demonstrated efficacy and may address access barriers to care. Participant characteristics have been shown to affect engagement with these programs; however, limited information is available about the relationship between participant characteristics and engagement with internet-based programs for self-management of chronic pain. The current study examined relationships between demographic and clinical characteristics and engagement with the Pain EASE program, a self-directed, internet-based cognitive behavioral therapy intervention for veterans with chronic low back pain (cLBP). Veterans with cLBP were enrolled in a 10 week trial of the Pain EASE program. Engagement measures included the number of logins, access to coping skill modules, and completed study staff-initiated weekly check-in calls. Regression analyses were conducted to identify significant predictors of engagement from hypothesized predictors (e.g., race/ethnicity, age, depressive symptom severity, and pain interference). Participants ( N = 58) were 93% male, 60.3% identified as White, and had a mean age of 54.5 years. Participants logged into the program a median of 3.5 times, accessed a median of 2 skill modules, and attended a median of 6 check-in calls. Quantile regression revealed that, at the 50th percentile, non-White-identified participants accessed fewer modules than White-identified participants ( p = .019). Increased age was associated with increased module use ( p = .001). No clinical characteristics were significantly associated with engagement measures. White-identified race/ethnicity and increased age were associated with greater engagement with the Pain EASE program. Results highlight the importance of defining and increasing engagement in internet-delivered pain care. Abstract : Among individuals with chronic low back pain, increased age and self-identifying as White were associated with increased engagement in an internet-based, self-guided chronic pain intervention.